2016
DOI: 10.1093/mnras/stw1422
|View full text |Cite
|
Sign up to set email alerts
|

The VIRUS-P Exploration of Nearby Galaxies (VENGA): spatially resolved gas-phase metallicity distributions in barred and unbarred spirals

Abstract: We present a study of the excitation conditions and metallicity of ionized gas (Z gas ) in eight nearby barred and unbarred spiral galaxies from the VIRUS-P Exploration of Nearby Galaxies (VENGA) survey, which provides high spatial sampling and resolution (median ∼ 387 pc), large coverage from the bulge to outer disc, broad wavelength range (3600-6800 Å), and medium spectral resolution (∼ 120 km s −1 at 5000 Å). Our results are: (1) We present high resolution gas excitation maps to differentiate between region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 169 publications
(338 reference statements)
9
74
2
Order By: Relevance
“…Hoopes et al 1996;Greenawalt 1998) or applying a fixed intensity threshold to remove all emission lower than a given value (e.g. Blanc et al 2009;Kaplan et al 2016). Including information about the spatial extent of HII regions can also help decomposing the emission into a diffuse background and compact sources (e.g.…”
Section: Diffuse Emissionmentioning
confidence: 99%
“…Hoopes et al 1996;Greenawalt 1998) or applying a fixed intensity threshold to remove all emission lower than a given value (e.g. Blanc et al 2009;Kaplan et al 2016). Including information about the spatial extent of HII regions can also help decomposing the emission into a diffuse background and compact sources (e.g.…”
Section: Diffuse Emissionmentioning
confidence: 99%
“…One complication to the Balmer decrement method is that Hα/Hβ is a function of temperature and density and we assume that the emission is coming from a star-forming region. However, diffuse ionized gas (DIG) which has non-local origins, also contribute Hα (see Kaplan et al 2016 for how they dealt with DIG emission in a sample of VENGA galaxies). Figure 6 shows the extinction maps derived from both methods as well as the non extinctioncorrected Hα map of NGC 2903.…”
Section: Treatment Of Dustmentioning
confidence: 99%
“…Next, we compare to observations of gas-phase metallicity radial gradients in the local universe. NGC 2903 is one of the galaxies that Kaplan et al (2016) studied. The authors found that seven out of the seven gas-phase metallicity indicators exhibit solar and super-solar values in the central region of NGC 2903, even reaching 0.4 dex above so-lar values.…”
Section: Stars In the Bulgementioning
confidence: 99%
“…via the PINGS and CALIFA surveys; Rosales-Ortega et al 2010;Sánchez et al 2012bSánchez et al ,a, 2014 and VIRUS-P (e.g. via the VENGA survey; Blanc et al 2013;Kaplan et al 2016). This push is particularly interesting from a galaxy evolution perspective, as MUSE effectively allows the study of galaxies inside a wider range of environments, including that of compact groups and clusters, with unprecedented spatial resolution.…”
Section: Introductionmentioning
confidence: 99%